From Strangers to Sun Bleached Flies: A Speech Act Analysis in Ethel Cain’s Lyrics - Syahrir, Muthia Amalia; Hasbi, Muhammad (Universitas Sulawesi Barat, 2024)
This research aims to explore the use of speech acts in Ethel Cain's Strangers and Sun Bleached Flies from her acclaimed album Preacher's Daughter. This study employs a descriptive qualitative research design that focuses on the analysis of Searle's speech act classification—declaratives, representatives, directives, expressives, and commissives—to uncover how Cain conveys complex emotional narratives related to trauma, identity, and familial relationships. This research uses library research to collect data from the lyrics of two of Ethel Cain’s selected songs, Strangers and Sun Bleached Flies. The data analysis process aligns with typical approaches in speech act analysis within linguistics, particularly in contexts where John Searle's taxonomy is applied to literary or artistic works like song lyrics. The findings reveal that speech acts are very useful for deciphering the complex meaning of music lyrics and suggest that Cain's nuanced use of language not only enhances the emotional depth of her music but also invites listeners to engage with themes of vulnerability and resilience. This study contributes to a deeper understanding of contemporary songwriting as a form of expressive communication.